Close-packing-based sensor node deployment schemes for AOFSN. (1st January 2011) - Peng, Li-Mei; Youn, Chan-Hyun; Tang, Wan; Li, Xin-Wan
The sensor node deployment schemes are considered for a hierarchical all-optical fibre sensor network (AOFSN), as it mainly affects the sensing accuracy. High sensing accuracy requires high coverage ratio and low blind ratio, while low sensing cost requires less number of sensor nodes/switches and low overlapping ratio. Considering the above requirements, we propose the close-packing based sensor node deployment (CPSD) scheme for two dimensions. Then the CestPSD scheme is extended to three dimensions and is named as 3-D CestPSD. AOFSN applying the 2-D/3-D CestPSD schemes can obtain maximum coverage and minimum blind ratio while maintaining no overlapping ratio. The reliability of AOFSN using 2-D/3-D CestPSD deployment is then discussed and improved by proposing efficient switch architectures and switch deployment schemes. The network performances of sensing accuracy and the reliability of AFOSN are numerically analysed and compared in terms of coverage ratio, overlapping ratio, blind ratio and node density.